Propaganda aspects of information about capturing cities. Gdańsk in 1945 on the pages of „Red Star” newspaper (City and War, 2021)
During the war, the intensification of information about a given city usually took place when it was conquered, when the winners could boast about their success and advantage over opponents. The most important elements of the disseminated information and propaganda were the orders and messages of the authorities, but the letters sent directly from the battlefield appealed to the recipients. The correspondents included in their texts the details of the clashes and presented the characters of heroes. The illustrations, especially the photos, were a significant enrichment to convince the truth of the presented narrative. Often this information was supplemented with publications about the history and importance of that city for the struggle. This article presents the battle of Gdańsk during the Second World War based on the Red Army reports, articles and photographs from the “Red Star”, newspaper for soviet soldiers, given in March and April 1945. The author, using the press, documents and literature of the subject, discusses propaganda aspects of war information on capturing large cities. He also shows the specific role of newspapers in totalitarian countries in informing soldiers on the front about further victories.